Effects of light on direct and indirect defences against herbivores of young plants of Mallotus japonicus demonstrate a trade-off between two indirect defence traits - Yamawo, Akira (Oxford University Press, 2010)
BACKGROUND AND AIMS: Although most studies on plant defence strategies have focused on a particular defence trait, some plant species develop multiple defence traits. To clarify the effects of light on the development of multiple defence traits, the production of direct and indirect defence traits of young plants of Mallotus japonicus were examined experimentally under different light conditions. METHODS: The young plants were cultivated under three light conditions in the experimental field for 3 months from May to July. Numbers of ants and pearl bodies on leaves in July were examined. After cultivation, the plants were collected and the developments of trichomes and pellucid dots, and extrafloral nectaries (EFNs) on the leaves were examined. On plants without nectar-collecting insects, the size of EFNs and the volume of extrafloral nectar secreted from the EFNs were examined. KEY RESULTS: Densities of trichomes and pellucid dots did not differ significantly among the plants under the different light conditions, suggesting that the chemical and physical defences function under both high and low light availability. The number of EFNs on the leaves did not differ significantly among the plants under the different light conditions, but there appeared to be a trade-off between the size of EFNs and the number of pearl bodies; the largest EFNs and the smallest number of pearl bodies were found under high light availability. EFN size was significantly correlated with the volume of extrafloral nectar secreted for 24 h. The number of ants on the plants was smaller under low light availability than under high and moderate light availability. CONCLUSIONS: These results suggest that direct defence traits function regardless of light conditions, but light conditions affected the development of indirect defence traits.